Pengembangan Modul Elektronik Berbasis SAVI Untuk Pembelajaran Bahasa Arab - Koderi Koderi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2017)
This study aims to develop SAVI-based electronic module (somatic, auditory, visual, intellectual) for Arabic learning in MTs. Using research development methods, Dick and Carey's model design is combined with the Hannafin and Peck model. Draft final model modified through four stages of preliminary research, design and model development, validation, evaluation and revision and implementation of effectiveness test model. Validation of design experts, material experts, media experts is in very good category. Validation of one to one learner, small group, field trial category is very good. The results of model effectiveness test obtained the average initial test value = 48.1666 final test = 73.775, the difference of initial test score and final test = 25,608. The result of tcount is bigger than ttable, that is 15,42807> 2.02268. This means that SAVI-based electronic module for learning Arabic in MTs effectively improves learners' learning outcomes. The final model of electronic module can be found at www.koderi-iain.my.id.